DINAMIKA BALAI KERAJAAN SAKSI-SAKSI YEHOVA DI KOTA MALANG - Trijuliani Renda (Balai Diklat Keagamaan Denpasar, 2021)
Abstrak The study of qualitative research results on Jehovah's Witnesses in Malang City with data collection methods carried out through interviews, observation and literature study to explore the phenomenon of SSY evangelism in Malang City. The research findings explain the existence of a sect in Christianity that is still controversial. The mainstream church refused to include SSY as part of Christianity because of its conflicting theological views. SSY has constitutional rights stipulated in the Law which confirms their position as a sect in Christianity. As a religious community, SSY, like other denominations in Christianity, has the right to worship and has the right to get a place of worship, as long as it meets the requirements required in PBM (Joint Regulation of the Minister of Religion and Minister of Home Affairs) NO 9 and 8 concerning the Construction of Houses of Worship.